We'll transform the sum in product using the
formula:
cos a + cos b = 2 cos[(a+b)/2]cos
[(a-b)/2]
We'll write the formula for a = x and b =
3x:
cos x + cos 3x = 2cos[(x+3x)/2]cos
[(x-3x)/2]
cos x + cos 3x = 2cos[(4x)/2]cos
[(-2x)/2]
cos x + cos 3x = 2cos[(2x)]cos
[(-x)]
Since the function cosine is even, we'll write cos
[(-x)] = cos x.
cos x + cos 3x = 2cos 2x*cos
x
We'll put 2cos 2x*cos x =
0
cos 2x = 0
2x = +/- arccos 0
+ 2kpi
2x = +/-pi/2 +
2kpi
x = +/- pi/4 +
kpi
cos x =
0
x = +/- pi/2 +
2kpi
The solutions of the
equation are: {+/- pi/4 + kpi}U{+/- pi/2 + 2kpi}.
No comments:
Post a Comment